2009
DOI: 10.1097/mlr.0b013e318195fce7
|View full text |Cite
|
Sign up to set email alerts
|

Family Oversight and the Quality of Nursing Home Care for Residents With Advanced Dementia

Abstract: Background-The quality of nursing home (NH) care for residents with advanced dementia has been described as suboptimal. One relatively understudied factor in the provision of NH care is the role of private oversight and monitoring by family members and friends.Objective-To examine the association between private oversight and the quality of end-of-life care for NH residents with advanced dementia.Research Design-This study employed longitudinal data on 323 NH residents with advanced dementia living in 22 Bosto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 30 publications
0
35
0
2
Order By: Relevance
“…Our finding that family members expressed a belief that visitation and vigilance were needed in order to ensure adequate resident care may shed light on prior findings from the CASCADE study which indicate that lack of family member visitation was associated with lower quality care. 24 This work also found that very high levels of visitation were associated with lower quality care, which may reflect the family members’ perceived need for greater oversight.…”
Section: Discussionmentioning
confidence: 68%
“…Our finding that family members expressed a belief that visitation and vigilance were needed in order to ensure adequate resident care may shed light on prior findings from the CASCADE study which indicate that lack of family member visitation was associated with lower quality care. 24 This work also found that very high levels of visitation were associated with lower quality care, which may reflect the family members’ perceived need for greater oversight.…”
Section: Discussionmentioning
confidence: 68%
“…Pårørendes involvering er sammensatt av alt fra besøk, sosio-emosjonell støtte, å vaere talsperson, til å gi personlig omsorg (Davies & Nolan, 2006). Pårørende bidrar til å ivareta beboernes livskvalitet, og det kan se ut som pårørendes involvering også er positivt for kvaliteten på pleien i sykehjemmene (Gaugler, 2005;Grabowski & Mitchell, 2009). Samtidig er det studier som viser at pårørende selv har varierende opplevelser av det å bli pårørende til beboere på sykehjem (Berglund, 2007;Førsund, 2009;Haesler, Bauer & Nay, 2010;Hertzberg, Ekman & Axelsson, 2001).…”
Section: Bakgrunnunclassified
“…Other analyses were cross sectional or did not include patients at the end of life (associations with satisfaction with care [115], instrument properties [128], cross sectional associations between grief and depression [120], and associations with family oversight (visiting) [119]). …”
Section: Us Nursing Homes Inmentioning
confidence: 99%
“…Newer and larger prospective studies include multicenter studies in the US (CASCADE; [44,64,95,115,[118][119][120]128]), the Netherlands (DEOLD; [60]), and Italy (EOLO-PSODEC; [108] [F Toscani, personal communication]; Table 1, studies 3, 4 and 6) typically performed after initial retrospective study. Prospective studies vary as to whether they include both patient and family outcome, and some of them have restricted enrollment to advanced dementia due to feasibility and priority issues.…”
Section: Research Trends In Dementia At the End Of Lifementioning
confidence: 99%